1992
DOI: 10.1172/jci115764
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in chronically inflamed human upper airway tissues express transforming growth factor beta 1 gene (TGF beta 1).

Abstract: Transforming growth factor , (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(131 citation statements)
references
References 32 publications
7
121
0
3
Order By: Relevance
“…Although TGF-b 1 levels are raised in the plasma of nonatopic asthmatics, this is not seen in atopic asthma [171]. TGF-b 1 levels are also increased in eosinophils from severe asthmatics at the mRNA level [172,173]. Recently, BALZAR et al [174] reported that there were more TGF-b 2 positive cells in endobronchial tissue biopsies from eosinophilic severe asthmatics.…”
Section: Involvement Of Tgf-b In Asthmamentioning
confidence: 99%
“…Although TGF-b 1 levels are raised in the plasma of nonatopic asthmatics, this is not seen in atopic asthma [171]. TGF-b 1 levels are also increased in eosinophils from severe asthmatics at the mRNA level [172,173]. Recently, BALZAR et al [174] reported that there were more TGF-b 2 positive cells in endobronchial tissue biopsies from eosinophilic severe asthmatics.…”
Section: Involvement Of Tgf-b In Asthmamentioning
confidence: 99%
“…Lineagespecific cytokine effects on differentiated cells, which retain hemopoietic cytokine receptors on their surface, result in "activation" or "phenotype switching": IL-3, IL-5, and GM-CSF can activate and prevent apoptosis of basophils and eosinophils (42,59); G-CSF and GM-CSF do the same for neutrophils (60). Autocrine stimulation by eosinophils, basophils, or mast cells of their own differentiation and/or activation is thus possible, since they produce a wide range of hemopoietic and proinflammatory cytokines, including IL-3, IL-4, IL-5, IL-6, and GM-CSF (33,(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Cytokines and Lineage Specgcitymentioning
confidence: 99%
“…1) (Miller el al, 1989;Gatherer et al, 1990;Millan et al, 1991;Schmid et al, 1991;Lea et al, 1992; Das et al, 1993). The northern analysis illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RNA (Ohno et al, 1992 (Mood et al, 1974). This analysis also assumes that the differences observed are not due to the fact that the tissues are situated on different slides.…”
Section: Tissuesmentioning
confidence: 99%
See 1 more Smart Citation